2013
DOI: 10.5539/ijc.v5n3p12
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based in Silico Study of 6-Gingerol, 6-Ghogaol, and 6-Paradol, Active Compounds of Ginger (Zingiber officinale) as COX-2 Inhibitors

Abstract: Ginger's (Zingiber officinale) phenolic compounds, that are 6-gingerol, 6-shogaol, and 6-paradol, have been proven to show anti-inflammatory activity. The purpose of this paper was to discover whether these compounds are potential to be used as COX-2 inhibitors through structure-based in silico study, which is based on the character of the receptor. Docking was performed to the binding pockets of both COX-1 and COX-2 enzymes, to examine their selective character on COX-2. The binding pockets used in this proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…One such alternative tool is the in silico drug design or the computer-aided drug design. In silico drug design can play a significant role in all stages of drug development from the preclinical discovery stage to late stage clinical development [19]. The results obtained in silico screening have shown that it represents the best way to get accurate results in a very short period and saving manner [20].…”
Section: Resultsmentioning
confidence: 99%
“…One such alternative tool is the in silico drug design or the computer-aided drug design. In silico drug design can play a significant role in all stages of drug development from the preclinical discovery stage to late stage clinical development [19]. The results obtained in silico screening have shown that it represents the best way to get accurate results in a very short period and saving manner [20].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed the use of Ginger as traditional medicine since immemorial decades as a curative for several diseases, including cancer, diabetes, bronchitis and arthritis… etc (Mashhadi et al, 2013). Several evidences had suggested that Ginger and its active constituents suppress the tumor cell growth, induces apoptosis in a variety of cancers (Radhakrishnan et al, 2014), inhibits vascular endothelial growth factor (VEGF), leads to the cell cycle arrest at G1 phase (Kim et al, 2005) and reduces the inflammatory molecules like Cyclooxgenease (COX2) (Saptarini et al, 2013). In the present manuscript, we hypothesize that Ginger/ its derivatives (6-Gingerol and 6-Shogaol) function as promising nutraceuticals to block both angiogenesis and lymphangiogenesis and metastatic progression.…”
Section: Introductionmentioning
confidence: 99%
“…Some molecular modeling and docking studies with ginger components have already been mentioned in sections 3.2 to 3.4 31,34,36 . These studies have demonstrated that the ginger component 6-gingerol can inhibit COX-2, leukotriene A4 hydrolase protein and serotonin receptor subtype 5-HT 1A .…”
Section: Molecular Modeling and Docking Studies With Ginger Componentsmentioning
confidence: 99%
“…Saptarini et al 31 have performed in silico docking of 6-gingerol, 6-shogoal and 6-paradol in the binding pockets of COX-1 and COX-2 enzymes. The binding site explored was identical to the binding site for the potent anti-inflammatory drugs flurbiprofen and SC-558.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%